2020
DOI: 10.1111/acel.13132
|View full text |Cite
|
Sign up to set email alerts
|

Plasma proteomic signature of the risk of developing mobility disability: A 9‐year follow‐up

Abstract: Introduction:Mobility disability is a powerful indicator of poor health in older adults.The biological and pathophysiological mechanism underlying the development of mobility disability remains unknown. This study conducted a data-driven discovery phase investigation to identify plasma proteins that predict the incidence of mobility disability in community-dwelling older adults without mobility disability at baseline. Methods:We investigated 660 women and men, aged 71.9 ± 6.0 (60-94) years, who participated in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
23
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 43 publications
5
23
1
1
Order By: Relevance
“…There is growing evidence in both human and animal models that GDF15 plays an important role beyond cardiovascular disease and has been linked with weight homeostasis, fibrosis, diabetes, cardiovascular disease, renal disease, mobility disability and cancer (27)(28)(29)(30)(31)(32). IL-6, a classical SASP factor in multiple senescent cell types (19), was also associated with allcause mortality.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is growing evidence in both human and animal models that GDF15 plays an important role beyond cardiovascular disease and has been linked with weight homeostasis, fibrosis, diabetes, cardiovascular disease, renal disease, mobility disability and cancer (27)(28)(29)(30)(31)(32). IL-6, a classical SASP factor in multiple senescent cell types (19), was also associated with allcause mortality.…”
Section: Discussionmentioning
confidence: 99%
“…In humans, GDF15 has been suggested as a biomarker of cardiovascular disease mortality, but more recently associated with all-cause mortality ( Lindholm et al, 2018 ; ActiFE study group et al, 2019 ). There is growing evidence in both human and animal models that GDF15 plays an important role beyond cardiovascular disease and has been linked to weight homeostasis, fibrosis, diabetes, cardiovascular disease, renal disease, mobility disability and cancer ( Baek and Eling, 2019 ; Bidadkosh et al, 2017 ; Daniels et al, 2011 ; Ho et al, 2013 ; Wallentin et al, 2013 ; Osawa et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Noteworthy, after the 5-year follow-up, more than half of the participants with ≥2 nutritional deficits became octogenarians whose mobility tends to decline faster than in younger people ( 17 ). On the other hand, our exploratory analysis found that LGI, an important mechanism implicated in both aging ( 37 ) and mobility disability ( 17 , 38 ), contributed to this accelerated decline of physical performance in older individuals with combined nutritional deficits. This finding suggests that both the presence of nutritional deficits and chronic inflammation contribute to physical impairment.…”
Section: Discussionmentioning
confidence: 81%
“…Similar to what has been done with the methylome, elastic regression or other multivariate methods can be used to compute a weighted average of protein concentrations that approximate chronological aging and show deviation from chronological aging in individuals in a trajectory of deteriorating health (Lehallier et al, 2019;Tanaka et al, 2020a). Studies are ongoing to identify proteins that in asymptomatic individuals predict the development of phenotypes typical of aging, such dementia (Tanaka et al, 2020b), frailty (Landino et al, 2020) and many other diseases (Osawa et al, 2020;Tanaka et al, 2020b).…”
Section: The Rationale For Using Proteomics In Building System Models In Humansmentioning
confidence: 99%